The Dietary Flavonoid Kaempferol Mediates Anti-Inflammatory Responses via the Src, Syk, IRAK1, and IRAK4 Molecular Targets. (2nd April 2015) - Kim, Shi Hyoung; Park, Jae Gwang; Lee, Jongsung; Yang, Woo Seok; Park, Gye Won; Kim, Han Gyung; Yi, Young-Su; Baek, Kwang-Soo; Sung, Nak Yoon; Hossen, Muhammad Jahangir; Lee, Mi-nam; Kim, Jong-Hoon; et al.
Abstract : Even though a lot of reports have suggested the anti-inflammatory activity of kaempferol (KF) in macrophages, little is known about its exact anti-inflammatory mode of action and its immunopharmacological target molecules. In this study, we explored anti-inflammatory activity of KF in LPS-treated macrophages. In particular, molecular targets for KF action were identified by using biochemical and molecular biological analyses. KF suppressed the release of nitric oxide (NO) and prostaglandin E2 (PGE2 ), downregulated the cellular adhesion of U937 cells to fibronectin (FN), neutralized the generation of radicals, and diminished mRNA expression levels of inflammatory genes encoding inducible NO synthase (iNOS), TNF- α, and cyclooxygenase- (COX-) 2 in lipopolysaccharide- (LPS-) and sodium nitroprusside- (SNP-) treated RAW264.7 cells and peritoneal macrophages. KF reduced NF- κ B (p65 and p50) and AP-1 (c-Jun and c-Fos) levels in the nucleus and their transcriptional activity. Interestingly, it was found that Src, Syk, IRAK1, and IRAK4 responsible for NF- κ B and AP-1 activation were identified as the direct molecular targets of KF by kinase enzyme assays and by measuring their phosphorylation patterns. KF was revealed to have in vitro and in vivo anti-inflammatory activity by the direct suppression of Src, Syk, IRAK1, and IRAK4, involved in the activation of NF- κ B and AP-1.